Perfil dos indivíduos que receberam atendimento pelo SAMU a vítimas de traumatismo crânioencefálico no município de Anápolis-GO - Meillyne Alves dos Reis; Geraldo Soares da Silva Filho; Thiago Fontes Medeiros; Constanza Thaise Xavier Silva; Najla Maria Carvalho de Souza; Gláucia Oliveira Abreu B. Meireles (UniEVANGÉLICA, 2018)
Objective: to trace the profile of the individuals who received care by the Mobile Emergency Care Service (SAMU) victims of traumatic brain injury (TCE), in the city of Anápolis-GO. Methods: This study was descriptive, documentary and retrospective. This study was based on the quantitative approach of 63 tokens for users of the traumatic brain injury service from January to December 2014. The data collected from the user files were tabulated in Microsoft Excel spreadsheets. From the database, descriptive statistics were performed with absolute and relative frequency. Results: Of the 63 visits performed by SAMU with diagnosis of TBI, 80.9% were male and 19.1% female. Age ranged from 21 to 40 years (31.7%) and the classification of risk of TBI showed that 41.3% of the individuals were at moderate risk of firearm perforation (20.6% ) followed by fall at the same level; and in relation to the clinical evolution of the users, 19% of the cases died due to TBI. Conclusion: It was concluded that in the study, the male gender with age between 21 and 40 years with moderate risk of TBI caused by firearm perforation and fall at the same level constitute a risk group. The profiles of care provided by SAMU to the victims of TBI are very important so that there is an improvement in the pre-hospital and intrahospital care and in educational campaigns more efficient for the population.